Cell-targeted vaccines: implications for adaptive immunity - Ung, Trevor; Rutledge, Nakisha S.; Weiss, Adam M.; Esser-Kahn, Aaron P.; Deak, Peter (Frontiers in Immunology, 2023)
Recent advancements in immunology and chemistry have facilitated advancements in targeted vaccine technology. Targeting specific cell types, tissue locations, or receptors can allow for modulation of the adaptive immune response to vaccines. This review provides an overview of cellular targets of vaccines, suggests methods of targeting and downstream effects on immune responses, and summarizes general trends in the literature. Understanding the relationships between vaccine targets and subsequent adaptive immune responses is critical for effective vaccine design. This knowledge could facilitate design of more effective, disease-specialized vaccines.